IMPLEMENTATION OF THE SOCIAL SERVICE PROGRAM IN THE REHABILITATION OF SOCIAL ASSISTANCE FOR DISABLED PEOPLE IN SIDOARJO REGENCY - Ahmad Zulkarnaen Miladi; Achluddin Ibnu Rochim; Adi Susiantoro (MAP Observer: Jurnal Penelitian Administrasi Publik, 2023)
In the existence of people with disabilities, there is still minimal attention from the community because they are often looked down upon or underestimated so their deficiencies often result in discrimination or bullying. On the other hand, people with disabilities also need to meet the needs of their lives. This researcher uses a qualitative method, this researcher uses various techniques, namely collecting data in the form of conducting interviews to obtain clear and accurate information regarding the focus of the existing problems. The purpose of this study was to find out the role of the Social Service in the Implementation of the Social Rehabilitation Program for Persons with Disabilities in Sidoarjo Regency. The conclusion obtained from this research is the distribution of social rehabilitation programs for the Sidoarjo Regency Social Service in fulfilling the rights of persons with disabilities with facilities and also allowances for people with disabilities. hard to create persons with disabilities who are dignified and able to live like society in general.